2013
DOI: 10.1523/jneurosci.4437-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Brain Microstructure Reveals Early Abnormalities more than Two Years prior to Clinical Progression from Mild Cognitive Impairment to Alzheimer's Disease

Abstract: Diffusion imaging is a promising marker of microstructural damage in neurodegenerative disorders, but interpretation of its relationship with underlying neuropathology can be complex. Here, we examined both volumetric and brain microstructure abnormalities in 13 amnestic patients with mild cognitive impairment (MCI), who progressed to probable Alzheimer's disease (AD) no earlier than 2 years after baseline scanning, in order to focus on early, and hence more sensitive, imaging markers. We compared them to 22 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
157
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(167 citation statements)
references
References 62 publications
9
157
0
1
Order By: Relevance
“…In these studies, longer path lengths were found in MCI [12] and mild AD [10,13], reflecting disrupted interactions of distant brain regions. This anterior-posterior disintegration has been explained by a breakdown of anatomical connections, e.g., through the cingulum bundle or the superior longitudinal fasciculus, which are particularly vulnerable in AD [97][98][99], and by an imbalance of parietal and frontal metabolism. The PCC in particular shows greater hypometabolism than frontal regions in AD [22,100].…”
Section: Disrupted Functional Coupling Of Prefrontal and Parietal Dmnmentioning
confidence: 99%
“…In these studies, longer path lengths were found in MCI [12] and mild AD [10,13], reflecting disrupted interactions of distant brain regions. This anterior-posterior disintegration has been explained by a breakdown of anatomical connections, e.g., through the cingulum bundle or the superior longitudinal fasciculus, which are particularly vulnerable in AD [97][98][99], and by an imbalance of parietal and frontal metabolism. The PCC in particular shows greater hypometabolism than frontal regions in AD [22,100].…”
Section: Disrupted Functional Coupling Of Prefrontal and Parietal Dmnmentioning
confidence: 99%
“…In a meta-analysis that compared DTI to hippocampal measurements, Clerx and colleagues revealed that the effective size of the hippocampal MD is better than that of hippocampal volume in distinguishing aMCI from controls, and MD values are more discriminatory than FA values [83] . Douaud and colleagues examined both volumetric and microstructural abnormalities and found that progressive aMCI patients have significantly smaller GM volume in the left CA region and significantly higher MD in the left hippocampus compared to stable aMCI patients [84] . These findings highlight the benefit of using information about microstructural damage and traditional GM volume to detect early, mild abnormalities in aMCI patients prior to clinical progression to AD [84] .…”
Section: Mri and Functional Mri Approaches In The Hippocampus Of Amcmentioning
confidence: 99%
“…Douaud and colleagues examined both volumetric and microstructural abnormalities and found that progressive aMCI patients have significantly smaller GM volume in the left CA region and significantly higher MD in the left hippocampus compared to stable aMCI patients [84] . These findings highlight the benefit of using information about microstructural damage and traditional GM volume to detect early, mild abnormalities in aMCI patients prior to clinical progression to AD [84] . Another recent study combined structural MRI and fMRI methods and demonstrated that aMCI patients show GM volume loss in the bilateral hippocampus and signifi cant decreases in the amplitude of low-frequency fluctuation (ALFF) in the left hippocampus.…”
Section: Mri and Functional Mri Approaches In The Hippocampus Of Amcmentioning
confidence: 99%
“…Previous studies on GM MD in AD reported increases of hippocampal MD and whole brain GM MD in subjects with mild cognitive impairment (MCI) as compared to healthy controls Eustache et al, 2016;Fellgiebel et al, 2004;Müller et al, 2005;Scola et al, 2010), as well as in MCI patients that converted to AD compared to MCI subjects that remained stable over a period of several years (Douaud et al, 2013;Fellgiebel et al, 2006;Scola et al, 2010;van Uden et al, 2016). In some studies, hippocampal diffusivity even demonstrated a higher diagnostic and prognostic accuracy than hippocampal volume (Fellgiebel et al, 2006;Kantarci et al, 2005;Müller et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…In this case, MD would represent the joint effect of microstructural changes and macrostructural brain atrophy. However, most of the studies using DTI data of healthy older and AD participants did not consider PVE at all Douaud et al, 2013;Eustache et al, 2016;Müller et al, 2007). One study stated that PVC was not necessary as the regions of interest (ROIs) were not located at the surface of the brain (Eustache et al, 2016).…”
Section: Introductionmentioning
confidence: 99%